Computer simulation of dust transport phenomena in a RF discharge - Kravchenko, O.Yu.; Yastrub, Yu.A.; Lisitchenko, T.Y. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Using computer simulation we study the dynamics of dust particles in an rf discharge considering the mutual influence of the dust component and plasma. Simulation of the discharge is carried in the frame of the two-dimensional model by PIC/MCC method. To describe the motion of particles it is used molecular dynamics method, which takes into account the main factors influencing the behavior of dust particles (electric and gravitational forces, the forces of friction with the ions and neutrals). The simulation results have shown that dust particles are trapped in locations where the forces acting on them are balanced. The equilibrium configuration of particles studied depending on their size and different pressures of neutral gas in microgravity conditions, and under laboratory conditions. It is shown that dust particles lead to a decrease in the jump of the mean potential in the electrode layers and a sufficiently large particles can significantly alter plasma parameters in the discharge. C помощью компьютерного моделирования исследуется динамика пылевых частиц в ВЧ-разряде с учетом взаимного влияния пылевой компоненты и плазмы. Моделирование разряда проводится в рамках двухмерной модели методом PIC/MCC. Для описания движения частиц используется метод молекулярной динамики, в котором учтены основные факторы, влияющие на поведение пылевых частиц (электрическая и гравитационная силы, силы трения с ионами и нейтралами). Результаты моделирования показали, что пылевые частицы захватываются в областях, где силы, действующие на них, уравновешиваются. Исследованы равновесные конфигурации частиц в зависимости от их размера при разных давлениях нейтрального газа как в условиях микрогравитации, так и в лабораторных условиях. Показано, что пылевые частицы приводят к уменьшению скачка среднего потенциала в приэлектродных слоях и при достаточно большом размере могут существенно изменять параметры плазмы в разряде. За допомогою комп’ютерного моделювання досліджується динаміка пилових частинок в ВЧ-розряді з урахуванням взаємного впливу пилової компоненти і плазми. Моделювання розряду проводиться в рамках двохвимірної моделі методом PIC/MCC. Для описання руху пилових частинок використовується метод молекулярної динаміки, в якому враховані основні фактори, що впливають на поведінку пилових частинок (електрична та гравітаційна сили, сили тертя з іонами та нейтралами). Результати моделювання показали, що пилові частинки захвачуються в областях, де сили, які діють на них, врівноважуються. Досліджено рівноважні конфігурації пилових частинок в залежності від їх розміру при різних тисках нейтрального газу як в умовах мікрогравітації, так і в лабораторних умовах. Показано, що пилові частинки приводять до зменшення скачка середнього потенціалу в приелектродних шарах та при достатньо великому розмірі можуть суттєво змінювати параметри плазми в розряді.